2023
DOI: 10.1002/brb3.3212
|View full text |Cite
|
Sign up to set email alerts
|

Persistent post‐COVID headache is associated with suppression of scale‐free functional brain dynamics in non‐hospitalized individuals

Nathan W. Churchill,
Eugenie Roudaia,
J. Jean Chen
et al.

Abstract: IntroductionPost‐acute coronavirus disease 2019 (COVID‐19) syndrome (PACS) is a growing concern, with headache being a particularly debilitating symptom with high prevalence. The long‐term effects of COVID‐19 and post‐COVID headache on brain function remain poorly understood, particularly among non‐hospitalized individuals. This study focused on the power‐law scaling behavior of functional brain dynamics, indexed by the Hurst exponent (H). This measure is suppressed during physiological and psychological distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Another study, focused on recovered COVID-19 patients around six months after hospital discharge, observed in comparison to healthy controls an increased ALFF (i.e., hyperactivity) in regions of the visual, language, and default mode network but decreased ALFF (i.e., hypoactivity) in regions of the paralimbic and executive network ( Li et al, 2023 ). A study in non-hospitalized COVID-19 patients four months after the infection observed altered functional brain dynamics – here characterized by the Hurst component, which is typically suppressed during physiological and psychological distress – in patients with persistent headache compared to patients without headache and healthy controls ( Churchill et al, 2023 ). Altered functional brain dynamics were particularly apparent in temporal, sensorimotor, and insular brain regions, and were accompanied by reduced functional connectivity and BOLD activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study, focused on recovered COVID-19 patients around six months after hospital discharge, observed in comparison to healthy controls an increased ALFF (i.e., hyperactivity) in regions of the visual, language, and default mode network but decreased ALFF (i.e., hypoactivity) in regions of the paralimbic and executive network ( Li et al, 2023 ). A study in non-hospitalized COVID-19 patients four months after the infection observed altered functional brain dynamics – here characterized by the Hurst component, which is typically suppressed during physiological and psychological distress – in patients with persistent headache compared to patients without headache and healthy controls ( Churchill et al, 2023 ). Altered functional brain dynamics were particularly apparent in temporal, sensorimotor, and insular brain regions, and were accompanied by reduced functional connectivity and BOLD activity.…”
Section: Resultsmentioning
confidence: 99%
“…Conklin et al ( Conklin et al, 2021 ) previously described a distribution of lesions on SWI MRI images in critically ill COVID-19, which was found to be similar in patients with hypoxic respiratory failure, sepsis, and disseminated intravascular coagulation. From our search results, only four studies compared their findings in COVID-19 to other patient groups ( Sollini et al, 2021 , Kim et al, 2023 , Fischer et al, 2022 , Churchill et al, 2023 ), with one showing similarities to patients with traumatic brain injury (TBI) in terms of white matter alterations ( Fischer et al, 2022 ). However, compared to COVID-negative patients with flu-like symptoms, COVID-19 patients do show perfusion abnormalities ( Kim et al, 2023 ) and altered functional brain activity ( Churchill et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies investigating functional brain activity in patients recovered from COVID-19 have been conducted using resting-state methods. Alterations in signal properties and functional connectivity have been found in COVID-19 patients, 55,56 and have been associated with hospitalization, 57 and persistent symptoms such as headaches, 58 persistent olfactory dysfunction 48,59,60 and other behavioral markers such as working memory performance, 61,62 anxiety, 63 psychotic-like experiences in adolescents, 64 and post-traumatic stress symptoms. 65 Also, some studies found no functional alteration in recovered COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%